2017
DOI: 10.6023/cjoc201703048
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Tetramate Macrolactams from the Marine-Derived Actinoalloteichus cyanogriseus WH1-2216-6

Abstract: dihydromaltophilin (2)、4-deoxydihydromaltophilin (3)、maltophilin (4)、xanthobaccin C (5)和 FI-2 (6), 其中 1 为新化合物. 评价了化合物 1~5 对人正常肝细胞 L-02 及人癌细胞 A549、MCF-7、Jurkat、BXPC-3、HCT-116、PANC-1 和 K562 的细胞毒活性, 结果表明: 化合物 1~5 对上述人癌细胞具有细胞毒活性, 其半数抑制浓度(IC 50)为 0.1~9.7 μmol•L-1 ;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Figure S11). A detailed comparison of one-dimensional (1D) and two-dimensional (2D) NMR spectroscopic data of 2 (Tables 1 and 2, Supplementary Figures S12-S18) and deOH-HSAF (8, Figure 1) revealed the same planar structure for 2 and 8 [27,30]. The relative configuration of 2 was deduced by proton coupling constants (Z∆ 2,3 J 2,3 11.5 Hz; E∆ 17,18 J 17,18 15.5 Hz; Table 1) and careful analysis of NOESY correlations (Figure 4, Supplementary Figures S17 and S18).…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 96%
See 2 more Smart Citations
“…Figure S11). A detailed comparison of one-dimensional (1D) and two-dimensional (2D) NMR spectroscopic data of 2 (Tables 1 and 2, Supplementary Figures S12-S18) and deOH-HSAF (8, Figure 1) revealed the same planar structure for 2 and 8 [27,30]. The relative configuration of 2 was deduced by proton coupling constants (Z∆ 2,3 J 2,3 11.5 Hz; E∆ 17,18 J 17,18 15.5 Hz; Table 1) and careful analysis of NOESY correlations (Figure 4, Supplementary Figures S17 and S18).…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 96%
“…ADI127-7 and AHMU CJ201 also contain Group I of PTM BGCs (Figure 2a), while no PTMs have been reported from them. Actinoalloteichus cyanogriseus WH1-2216-6 was reported to produce HSAF and its analogues [27]; however, its genome sequence is not yet publicly available.…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…However, compounds 130 and 127 were most effective in their antifungal activities, with MIC values of 1.56 and 3.125 µg/mL. It was indicated that the 3-OH and 14-OH group of 5/,5/6-PTMs possibly contributed to antifungal activity, while the 16-OH group decreased bioactivity[117]. In the same year, chemical and genetic profile analyses of the marine cone-snail-associated Streptomyces CMB-CS038 yielded four 5/5/6 PTMs, 130, and three minor co-metabolites, 128, as well as the frontalamide precursor FI-3 (132) and a new HSAF derivate, with a novel mechanism of action and observable cytotoxicity[100,118,119].The activation of the silent PTM gene clusters of the Streptomyces pactum SCSIO 02999 by genome-mining led to the production of six new PTMs, 5/5/6-PTMs (pactamide A, B, D, and F)(134, 135, 137, and 139), 5/5-PTM (pactamide C 136), and 5-PTM (pactamide E 138), which (except for compounds 135 and 137) displayed potent or moderate cytotoxic activity against the four HTCLs of IC 50 = 0.24-8.7 µM [120].…”
mentioning
confidence: 99%
“…Among them, compound 126 revealed the most selective cytotoxicity against seven HTCLs, with IC 50 = 4.5-9.7 µM (selectivity index = 24.3-51.4) [117]. Compounds 127, 128, 130, and 131 also displayed antifungal activity (Aspergillus fumigatus AF293), with MIC = 1.56-25.0 µg/mL[117]. However, compounds 130 and 127 were most effective in their antifungal activities, with MIC values of 1.56 and 3.125 µg/mL.…”
mentioning
confidence: 99%